THE FIGHT AGAINST HUMAN TRAFFICKING BY UKRAINIAN LAW ENFORCEMENT AGENCIES (1991 – 2014) - KAZAN, Emiliia; MALIYK , Vasyl (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose is to do the research on the organizational and legal foundations of combating human trafficking, the activities of the Ukrainian law enforcement agencies in this area from independence of Ukraine (1991) to the beginning of the Russo-Ukrainian war (2014). The methodology of the research is based on general and special methods of scientific knowledge. In the process of the research, general scientific methods of deduction and induction, analysis and synthesis have been used. The comparative legal method has been applied during the analysis of regulatory legal acts related to the problem of human trafficking. The historical comparative method has been used to study the patterns and prerequisites of human trafficking. The qualitative and quantitative analysis of the issue under study has been done due to the use of the statistical method. The scientific novelty of the study consists in a retrospective analysis of the legal counteraction means to human trafficking in the national legislation of Ukraine and its practical implementation in the activities of law enforcement agencies. Conclusions. Human trafficking is a manifestation of a transnational crime and at the same time one of the most shameful violations of human rights and freedoms. Given the international scale of this problem, democratic states focus on combating this phenomenon, adopting a number of international legal acts aimed at prohibiting human trafficking in all its possible manifestations and interstate cooperation. Ukraine has implemented conventions and protocols aimed at preventing and combating trafficking in human beings of the UN and the Council of Europe. Ukraine is also one of the first countries in Europe to criminalize trafficking in people in 1998. Gradually, Ukraine updated national legislation, in particular the Criminal Code, to comply with international standards on the specified issue. The internal affairs bodies of Ukraine play an important role in combating human trafficking. Since 2000, specialized units for combating crimes related to human trafficking had operated within the structure of the Criminal Investigation Department of the Ministry of Internal Affairs and regional departments. Later, it was transformed into the Department for Combating Crimes Related to Human Trafficking. The Main Department for Combating Organized Crime (HUBOZ) is also within the structure of the Ministry of Internal Affairs. The Ukrainian law enforcement officers cooperate with international law enforcement agencies and national law enforcement agencies. Joint operational developments are implemented regarding transnational criminal organizations involved in human trafficking, exchange of operational information; planning and implementation of joint operations, which are carried out under the leadership of Europol, the Regional Centre of the South-East Europe Cooperation Initiative (SECI) in the fight against international crime, with HUAM, etc. A new challenge for the state was the beginning of the Russian Federation’s war against Ukraine in 2014, as the number of people “vulnerable to human trafficking” increased, especially among internally relocated people. Data from international organizations show a quantitative increase of several percent at the beginning of the conflict, while qualitative studies have shown the emergence of new types of exploitation: recruitment into the military formations of the LPR-DPR, work under military conditions. Key words: law enforcement agencies, Ministry of Internal Affairs, regulatory documents, combating human trafficking, combating crimes related to human trafficking, Main Department for Combating Organized Crime, military aggression of the Russian Federation in Ukraine in 2014.